2016
DOI: 10.1017/s1368980016000914
|View full text |Cite
|
Sign up to set email alerts
|

Dietary acculturation among the South-Asian Surinamese population in the Netherlands: the HELIUS study

Abstract: Objective: To test Koctürk's model of dietary change among South-Asian Surinamese in the Netherlands. The model categorizes foods into staple, complementary and accessory foods and postulates that dietary change after migration begins with accessory foods while foods associated with ethnic identity (staple foods) change at a slower rate. Design: Cross-sectional data from the HELIUS study. Dietary intake was assessed with an FFQ. Acculturation was based on social contacts and sense of belonging and was translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Retention of elements of traditional diets could explain higher diet quality among migrants compared with Dutch participants, assuming that the Western diet is less healthy [25]. This could also explain inconsistent socioeconomic patterning of diet quality among ethnic minority groups, if components of the traditional diets are retained as a way of expressing cultural identity, regardless of socioeconomic position [5]. Cultural expectation of hospitality [26], and the food preferences of family and friends, especially in collectivist cultures, may also prevent or slow shifts in dietary habits from the traditional diet.…”
Section: Interpretation Of Findings and Implications For Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Retention of elements of traditional diets could explain higher diet quality among migrants compared with Dutch participants, assuming that the Western diet is less healthy [25]. This could also explain inconsistent socioeconomic patterning of diet quality among ethnic minority groups, if components of the traditional diets are retained as a way of expressing cultural identity, regardless of socioeconomic position [5]. Cultural expectation of hospitality [26], and the food preferences of family and friends, especially in collectivist cultures, may also prevent or slow shifts in dietary habits from the traditional diet.…”
Section: Interpretation Of Findings and Implications For Policymentioning
confidence: 99%
“…Prevalence of disease is often higher in ethnic minority groups, and socioeconomic position is on average lower [4], so poorer diet quality among these groups may be expected. Dietary patterns and dietary behaviours differ between ethnic groups [5,6], which could contribute to ethnic differences in diet quality, and could also modify the relationship between socioeconomic position and diet [7]. These relationships warrant further study, as interventions and policies aiming to improve population diet quality and reduce dietary inequalities should take subgroup differences into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Findings of this study are consistent with previous studies that showed traditional staples of migrants remained important components of their diets. 3,4 However, findings in this study indicated that although plantain, roots, and tubers were still consumed in Europe, bread and cereals were the most important sources of staples, contributing to almost half of the total staple intake of Ghanaian migrants in Europe. Similar to a qualitative study 27 conducted among Ghanaian migrants in Berlin, this study also demonstrated a shift from a fish-based diet in Ghana to a more meat-based one in Europe.…”
Section: Evidence For Dietary Change With Migrationmentioning
confidence: 63%
“…Several studies 3,35,36 showed consistent associations between acculturation and diet irrespective of the acculturation strategy used. However, a key finding from this study is that associations between acculturation and dietary intake differed according to the acculturation proxy that was applied.…”
Section: Evidence For Dietary Change With Migrationmentioning
confidence: 98%
“…The Canadian Community Health Survey showed two different outcomes: data from 2009 revealed that immigrants consumed less F&V than those born in Canada [ 54 ], while data from 2007 found no statistically significant difference in F&V intake between immigrants and Canadians [ 55 ]. In two other studies conducted in the Netherlands, results showed that South Asian (Surinamese and Pakistanis) generally reported lower frequency of fruit and vegetables compared with the Dutch population [ 56 , 57 ]. The Oslo Immigrant Health Profile from 2008, showed that Vietnamese men had the lowest and Turkish women the highest consumption of F&V, while Norwegians were neither the end nor the beginning of spectrum [ 36 ].…”
Section: Discussionmentioning
confidence: 99%